Ateroma arteri karotis pada radiograf panoramik sebagai diagnosis awal aterosklerosis - Dwi Putri Wulansari; Farina Pramanik (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: This review aimed to understand the radiographic features of carotid artery atheroma on panoramic radiographs as an early diagnosis of atherosclerosis. Literature Review: Carotid artery calcification is caused by a plaque known as an atheroma. Atheroma is a plaque composed of lipids and rich in calcium. If atheroma formation in the carotid arteries increases, it would cause stenosis of the blood vessels and increase the risk of stroke. On panoramic radiographs, carotid artery atheroma appears as a heterogeneous radiopaque image with an irregular shape and well-defined borders. Radiopaque image located inferior to the angle of the mandible, close to the cervical spine (C3-C5) and above the hyoid bone. Conclusion: Incidental findings on panoramic radiograph could be an initial reference for further examination and evaluation of atherosclerosis.